Pengaruh Good Governance terhadap Kualitas Laporan Keuangan dengan Kompetensi SDM sebagai Variabel Moderasi pada GKJW Rejoagung - Septa Krisanatalia; Suwignyo Widagdo; Mainatul Ilmi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This study aims to determine the influence of the principle of accountability, the principle of transparency, and the principle of responsibility for Good Governance on the quality of financial statements with the competence of human resources as a moderation variable in Greja Kristen Jawi Wetan Rejoagung, Semboro District, Jember. The method of data collection in this study is the distribution of questionnaires to church administrators and staff that are directly related to church finances. The population used in this study is church administrators and staff who are directly related to church finances with a population of 20 people. The sample return technique used is a saturated sampling technique. The analysis method used is moderated regression analysis (MRA). The results showed that the principle of transparency and the principle of responsibility affect the quality of financial statements while the principle of accountability does not affect the quality of financial statements. Human resource competence cannot moderate the relationship of accountability to the quality of financial statements, but human resource competence can moderate transparency and responsibility for the quality of financial statements.